Characteristics of the nonpulmonary vein foci induced after second‐generation cryoballoon ablation for paroxysmal atrial fibrillation - Kato, Nobutaka; Nitta, Junichi; Sato, Akira; Inamura, Yukihiro; Takamiya, Tomomasa; Inaba, Osamu; Negi, Ken; Takahashi, Yoshihide; Goya, Masahiko; Sasano, Tetuo (Journal of cardiovascular electrophysiology, 2020)
Introduction Pulmonary vein isolation (PVI) using cryoballoon is effective for patients with paroxysmal atrial fibrillation (PAF); however, few reports have evaluated the non‐pulmonary vein (PV) foci after cryoballoon ablation. We aimed to evaluate the characteristics of non‐PV foci and predictors of atrial fibrillation (AF) recurrence after cryoballoon ablation. Methods and Results This was a single‐center retrospective study of 647 patients with PAF who underwent initial PVI using a second‐generation cryoballoon. After PVI, all patients underwent high‐dose isoproterenol infusion to assess the existence of non‐PV foci. Non‐PV foci were observed in 211 patients (32.6%), which were most frequently observed in the superior vena cava. Higher age (odds ratio [OR] = 1.02; 95% confidence interval [CI] = 1.00‐1.04; P = .025), female sex (OR = 1.65; 95% CI = 1.13‐2.41; P = .009), and lower body mass index (OR = 0.95; 95% CI = 0.89‐1.00; P = .049) were significantly associated with non‐PV foci. The existence of non‐PV foci was an independent predictor of AF recurrence (Hazard's ratio = 1.70; 95% CI = 1.12‐2.60; P = .014). When non‐PV foci were mappable and successfully ablated, patients with non‐PV foci showed similar outcomes with those without non‐PV foci (1‐year AF‐free survival rates of 88.5% vs 91.5%; P = .338). Conversely, when we failed to detect and eliminate non‐PV foci because they had multiple origins and were not consistently inducible (multichanging non‐PV foci), the 1‐year AF‐free survival rate was 56.4% even after substrate modification. Conclusion Non‐PV foci were observed in one‐third of patients with PAF after cryoballoon ablation and were associated with AF recurrence. Catheter ablation for non‐PV foci was effective when they were mappable; however, multichanging non‐PV foci were associated with worse prognosis.